Feminist Challenges to Conceptions of God: Exploring Divine Ideals - Anderson, P (2007)
This paper presents a feminist intervention into debates concerning the relation between human subjects and a divine ideal. I turn to what Irigarayan feminists challenge as a masculine conception of 'the God's eye view' of reality. This ideal functions not only in philosophy of religion, but in ethics, politics, epistemology and philosophy of science: it is given various names from 'the competent judge' to the 'the ideal observer' (IO) whose view is either from nowhere or everywhere. The question is whether, as Taliaferro contends, my own philosophical argument inevitably appeals to the impartiality and omni-attributes of the IO. This paper was delivered during the APA Pacific 2007 Mini-Conference on Models of God. © 2007 Springer Science + Business Media B.V.